Activation volume of the elastic-plastic transition in molecular crystals - Kiran, Mangalampalli S. R. N. (2022)
Nanoindentation experiments with a spherical indenter tip were performed on the major faces of l-alanine, p-nitroaniline, dl-tartaric acid, and sulfathiazole single crystals to measure the load at which an elastic-to-plastic deformation transition occurs, which is marked by a discrete displacement burst or pop-in. Large data sets (containing more than 100 points each) of the experimentally measured first pop-in loads, P1, were generated. By assuming that the statistical distribution in P1 is a consequence of the thermal fluctuations affecting the nucleation rate of incipient plastic events underneath the indenter, the activation volumes, λ, for the elastic-plastic transition are determined. For the four molecular crystals examined, λ values vary between 106 and 173 Å3, which are more than an order of magnitude than those in crystalline metals. However, they are similar to the molecular volume, ψ. A linear relationship between λ and ψ suggests that the plastic deformation in molecular crystals is intimately linked to the size of the molecules. These results are discussed in the context of slip planes and their orientations to the indentation direction, interplanar spacings, intermolecular interactions, etc.